A Study of Ursodeoxycholic Acid for Dissolution of Gallstones - Uddin, SM Afzal; Rahman, MK; Khan, MMR; Tarik, M Hasan; Haque, M Zahirul; Basak, PM; Rahman, M Moksedur; Islam, M Akhtarul; Huda, MN; Begum, Shahana (TAJ: Journal of Teachers Association, 2018)
Background: Gallstone disease one of the major health problems and causes of morbidity in Bangladesh as well as worldwide. Ursodeoxycholic acid is a bile acid which is used for dissolving gallstones. Objectives: To observe dissolution of gallstones among the patients of gallstone disease by use of ursodeoxycholic acid. Methods: It was a cross-sectional observational study carried out in the Department of Medicine, Rajshahi Medical College Hospital, Rajshahi from July, 2014 to June, 2016. According to inclusion and exclusion criteria 12 people having gallstone disease were selected whose stone size were <10mm and were treated withUrsodeoxycholic acid (Dosage of 8-12mg/kg/day). Thorough history, physical examination along with Ultrasonographical assessment were done for this study. Results: Complete gallstonedissolution with Ursodeoxycholic acid occurred in 08(66.67%) cases whereas dissolution did not occur in 04(33.33%) cases among the patients of gallstone diseases. Conclusion: In this study, complete dissolution of Gallstones (<10mm) occurred in 66.67% patients. TAJ 2014; 27(2): 27-29